Mimetic set and match: Around Shaffer’s “Sleuth” - Andrzej Fretschel-Hojarski (Studia Filmoznawcze)
Anthony Shaffer’s mystery thriller, Sleuth, and subsequent film version, provide a blueprint for the crushing influence of imitation and monstrous doubling as outlined by French-American anthropologist, René Girard. The relationship between crime writer Andrew Wyke and his wife’s lover reveals itself to be one of negative reciprocity built upon envy, leading to a lethal dénouement. Yet Milo’s final renunciation of mediated desire and further games-playing breaks the cycle of symmetry. Throughout both the script and screenplay, Shaffer offers an acute social commentary on the concepts of difference and non-belonging, while also addressing the drive towards assimilation which risks fomenting resentment among in-groups and out-groups.